Non-sedated functional imaging based on deep synchronization of PROPELLER MRI and NIRS. (July 2019) - Deng, Liang; Zhang, Juntian; Chen, Jitao; Yu, Zhihao; Zheng, Junrong
Highlights: NIRS signals are used in MRI data processing to correct imaging misalignments (referred as "deep synchronization" of both). Non-sedated functional imaging in a multi-modality framework are performed. The "deep synchronization" scheme performed better than "post synchronization" of MRI and NIRS. An eigenfunction model is proposed to quantify the time resolution of the hemodynamic response for temporal co-registration. Abstract: Background and Objective: Periodically rotated overlapping parallel lines with enhanced reconstruction-echo planar imaging (PROPELLER-EPI) is a promising technique for non-sedated functional imaging due to its unique advantage of motion correction. However, its multiple-blades sampling blood-oxygen-level dependent (BOLD) signal leads to low sampling rate and aliasing of higher frequency physiological signal components such as the cardiac pulsation. Methods: In this study, we use near infrared spectroscopy (NIRS) synchronized with pulse sequences of PROPELLER-EPI, utilizing the fact that the optical sensing speed is inherently high. NIRS measures changes of oxyhemoglobin and deoxyhemoglobin to identify the transient states of on-BOLD and off-BOLD, and then labels each blade by temporal co-registration. The labeled blades from multiple epochs of a functional experiment are then used for the k -space data combination and subsequent image reconstruction. An eigenfunction model is proposed for temporal co-registration and to quantify the temporal resolution of the hemodynamic response. Result: The experiment of NIRS labeled PROPELLER-EPI was carried out with the optical sampling rate of 10 Hz and the magnetic pulses repetition time of 1000 ms, and the temporal resolution is 20 times better than that of the state-of-the-art sliding-window PROPELLER-EPI. We compared the functional imaging results against the conventional magnetic resonance echo planar imaging-measured activity and achieved an accuracy of 0.9. Conclusions: Using the synchronization of NIRS, the proposed imaging scheme provides an effective way to implement PROPELLER-EPI, which features motion free, high SNR, and enhanced spatial-temporal resolution.